Distributed parallel computation for complex rotational flows of non-Newtonian fluids - Baloch, A.; Webster, M. F. (International journal for numerical methods in fluids, 2003)
Complex rotational flows of non‐Newtonian fluids are simulated through finite element methods. The predictions have direct relevance to dough kneading, associated with the food industry. The context is taken as two‐dimensional and one of stirring material within a cylindrical vessel. Three stirrer shapes are considered, placed in eccentric location with respect to the cylinder centre. The motion is driven by the rotation of the outer vessel wall. Variation with change in rheology and change in stirrer shapes are analysed, with respect to flow kinematics, stress fields, rate‐of‐work and power consumed. Computations are performed for Newtonian, shear‐thinning and viscoelastic fluids, at various viscosity levels to gradually approximate more realistic dough‐like response. For viscoelastic fluids, Phan‐Thien/Tanner constitutive models are adopted. The numerical method employed is based on a finite element semi‐implicit time‐stepping Taylor–Galerkin/pressure‐correction scheme, posed in a cylindrical polar co‐ordinate system. Simulations are conducted via distributed parallel processing, performed on a networked cluster of workstations, employing message passing. Parallel performance timings are compared against those obtained working in sequential mode. Ideal linear speed‐up with the number of processors is observed for viscoelastic flows under this coarse‐grained implementation. Copyright © 2003 John Wiley & Sons, Ltd.